Psychological Responses and Strategies Towards the COVID-19 Pandemic Among Higher Education Students in Portugal and Switzerland: A Mixed-Methods Study - Schwander-Maire, Françoise; Querido, Ana; Cara-Nova, Tanya; Dixe, Maria Anjos; Aissaoui, Djamel; Charepe, Zaida; Christie, Derek; Laranjeira, Carlos (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic has caused overwhelming changes in individual and community daily-life, resulting from the public health measures implemented to contain it, and also from its psychological and socio-economic consequences. These shifts and consequences impacted the entire population, but some groups are more likely to be affected by these changes, including higher education students. Objectives: a) to investigate mental health status and its determinants among higher-education students in Portugal and Switzerland; and b) to explore adjustment patterns used by these students to overcome the impact of the COVID-19 pandemic. Methods: A cross-sectional study with a mixed-methods sequential explanatory design was conducted in two phases. First, an online survey was conducted among higher education students in Portugal and Switzerland, in Portuguese and French respectively. A convenience sampling method was used. Second, some participants from the first phase were invited to participate in four online focus group discussions (two in each country) using a maximum variation sampling method. Results: The survey was answered by 1880 students. Portuguese students revealed higher levels of stress and anxiety, but lower depression symptoms and less resilient coping compared to Swiss respondents. Hope was identified as an explanatory variable for mental health symptoms in students from both countries. In the focus groups (n=27), 13 adjustment strategies were found, which were subdivided into three spheres: personal, social, and contextual. Conclusions: The results suggest that the COVID-19 pandemic had a mild to moderate impact on most of the evaluated mental health variables. Nevertheless, the students reacted and mobilized positive short-term strategies, which need to be reinforced in order to prevent long-term psychological harm. In addition, our results can inform psychosocial interventions to minimize psychological impact, anxiety, depression, and stress due to sanitary crises or other population-wide problems or disasters.